Effect of Fertilization on Growth of Poplar Clones in Nursery - Singh, Gurparteek; Singh, Tarsem; Singh, Avtar (International Journal of Bio-resource and Stress Management, 2019)
The effect of N, P and K fertilizer treatments was observed on poplar plants in nursery. The nutrients applied in combination to poplar had significant effect on height and collar diameter of entire transplants of poplar (ETP’S) produced in nursery. The nutrient treatment N225P150K75 was effective to increase in plant height, collar diameter, average leaf area and biomass of ETP’s produced. Among different clones studied clone no. L-47/48 and PL-6 attained maximum height, collar diameter, average leaf area and biomass. The minimum height was recorded in clone PL-1 and Collar diameter in clone PL-2. The average leaf area varied differently in the nine clones studied in the present investigation. The nutrient applied had significant effect on average leaf area of poplar in nursery. The maximum leaf area was recorded with the application of N150 P100 K50.The biomass produced by the poplar clones under the influence of nutrient applied to Poplar clones in nursery had similar response as to average leaf area. The interaction effect (clone×nutrients) shows that each clone has differential response to nutrient applied in different combinations of N, P and K treatment(N0P0K0), (N75P50K25), (N150P100K50) and (N225P150K75) for plant height, collar diameter, average leaf area and biomass growth. This interaction effect is reflection of genetic potential of clones under favourable G×E interaction.